Solitary Plasmacytoma of Mandible - Report of 2 Cases - Sekar, B.; Augustine, Dominic; Murali, S. (International Journal of Pathology, 2018)
A plasmacytoma is a discrete, solitary mass of neoplastic monoclonal plasma cells in either bone or soft tissue (extramedullary). Solitary plasmacytomas can be divided into 2 groups according to location, plasmacytoma of the skeletal system (SBP) and extramedullary plasmacytoma (EMP) respectively. Less than 5% of patients with a plasma cell dyscrasia present with a single bone (SBP) or extramedullary plasmacytoma (EMP).We present 2 rare cases of solitary plasmacytoma of bone affecting the mandible of 60 year old female and a 58 year old male